Somatic MIWI2 Hinders Direct Lineage Reprogramming From Fibroblast to Hepatocyte. (28th February 2019) - Shi, Xiaojie; Xiao, Zipei; Zonta, Francesco; Wang, Wei; Wan, Yue; Li, Yu; Wang, Nan; Kuang, Yuanyuan; Du, Mingjuan; Dong, Jian; Wang, Ju; Yang, Guang
Abstract : Remodeling of the gene regulatory network in cells is believed to be a prerequisite for their lineage reprogramming. However, its key regulatory factors are not yet elucidated. In this article, we investigate the role of PIWI proteins and provide evidence that one of them, MIWI2, is elicited during transdifferentiation of fibroblasts into hepatocyte-like cells. In coincidence with the peak expression of MIWI2, we identified the appearance of a unique intermediate epigenetic state characterized by a specific Piwi-interacting RNA (piRNA) profile consisting of 219 novel sequences. Knockout of MIWI2 greatly improved the formation of the induced hepatocytes, whereas overexpression of exogenous MIWI2 completely abolished the stimulated effect. A bioinformatics analysis of piRNA interaction network, followed by experimental validation, revealed the Notch signaling pathway as one of the immediate effectors of MIWI2. Altogether, our results show for the first time that temporal expression of MIWI2 contributes negatively to cell plasticity not only in germline, but also in developed cells, such as mouse fibroblasts. Stem Cells 2019;37:803–812 : Abstract : The role of MIWI2 in transdifferentiation of somatic cells unveils an intermediate cellular state characterized by the biogenesis of piRNAs. Jag1-Notch signaling is shown to be one of the immediate downstream effector pathways. (iHep: induced hepatocyte. TFs: transcription factors)